Ixekizumab—An Effective and Safe Treatment for Moderate-to-Severe Plaque Psoriasis in Patients Previously Treated With Other IL-17 Inhibitors: Results From IXORA-P. Issue 4 (October 2019) - Papp, Kim; Blauvelt, Andrew; Sullivan, John; Tada, Yayoi; Polzer, Paula; Mallbris, Lotus; Zhang, Lu; Hong, Chi-ho
Background: The impact of treatment with interleukin 17 (IL-17) inhibitors on the efficacy of subsequent IL-17 inhibitor therapy is unknown. Objective: To evaluate the impact of previous treatment with IL-17 inhibitors on the 52-week efficacy of ixekizumab in patients with moderate-to-severe psoriasis. Methods: In a phase 3, randomized, double-blinded trial (IXORA-P; NCT02513550), patients with moderate-to-severe plaque psoriasis were randomized (2:1:1) to ixekizumab 80 mg every 2 weeks (IXE Q2W, n = 611), every 4 weeks (IXE Q4W, n = 310), or IXE Q4W/IXE Q2W dose adjustment (per predefined criteria; n = 306). Psoriasis Area and Severity Index 75%, 90%, and 100% response rates (PASI 75, PASI 90, and PASI 100) were assessed. Results: Overall, 288 (23.5%) of 1227 patients were IL-17 inhibitor experienced (brodalumab, 22.6%; secukinumab, 1.1%). The PASI 75, 90, and 100 at week 52 were similar between IL-17 inhibitor-naive and IL-17 inhibitor-experienced patients. The PASI 75 at week 52 for IL-17 inhibitor-naive and -experienced patients was 85% and 89% (IXE Q2W), 79% and 81% (IXE Q4W), and 83% and 85% (IXE Q4W/IXE Q2W), respectively. The PASI 90 at week 52 for IL-17 inhibitor-naive and -experienced patients was 79% and 82% (IXE Q2W), 65% and 67% (IXE Q4W), and 73% and 75% (IXE Q4W/IXE Q2W), respectively. The PASI 100 at week 52 for IL-17 inhibitor-naive and -experienced patients was 60% and 59% (IXE Q2W), 44% and 42% (IXE Q4W), and 49% and 52% (IXE Q4W/IXE Q2W), respectively. Safety findings were generally similar between IL-17 inhibitor-naive and -experienced patients. Conclusion: Ixekizumab was demonstrated to be an effective and safe therapeutic option for patients previously treated with other IL-17 inhibitors.